Molecular Drug Targets in Candida glabrata - Gupta, Payal; Rai, Nishant; Kumar, Navin (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92897);" role="presentation">Incidence of candidiasis has i<span dir="ltr" style="left: calc(var(–scale-factor)*192.53px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.84993);" role="presentation">ncreased <span dir="ltr" style="left: calc(var(–scale-factor)*230.69px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99871);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*241.61px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869252);" role="presentation">past decade. E<span dir="ltr" style="left: calc(var(–scale-factor)*300.67px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909782);" role="presentation">pidemi<span dir="ltr" style="left: calc(var(–scale-factor)*328.27px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960559);" role="presentation">ology is reported shifting from <span dir="ltr" style="left: calc(var(–scale-factor)*457.06px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929218);" role="presentation">albicans <span dir="ltr" style="left: calc(var(–scale-factor)*494.26px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936671);" role="presentation">to non- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929218);" role="presentation">albicans <span dir="ltr" style="left: calc(var(–scale-factor)*110.66px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928884);" role="presentation">Candida <span dir="ltr" style="left: calc(var(–scale-factor)*149.90px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986394);" role="presentation">(NAC) species like <span dir="ltr" style="left: calc(var(–scale-factor)*235.61px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990277);" role="presentation">C. glabrata<span dir="ltr" style="left: calc(var(–scale-factor)*283.97px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01913);" role="presentation">, which <span dir="ltr" style="left: calc(var(–scale-factor)*320.23px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939405);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*331.63px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969153);" role="presentation">intrinsic<span dir="ltr" style="left: calc(var(–scale-factor)*364.39px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00733);" role="presentation">ally <span dir="ltr" style="left: calc(var(–scale-factor)*384.07px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878068);" role="presentation">resistant <span dir="ltr" style="left: calc(var(–scale-factor)*422.14px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964299);" role="presentation">to azole drugs. N<span dir="ltr" style="left: calc(var(–scale-factor)*497.14px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996375);" role="presentation">o new <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911746);" role="presentation">antifungal has come into practice <span dir="ltr" style="left: calc(var(–scale-factor)*207.53px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89809);" role="presentation">from last decade. <span dir="ltr" style="left: calc(var(–scale-factor)*278.81px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925066);" role="presentation">Rising resistance to existing antifungal (in clinical isolates <span dir="ltr" style="left: calc(var(–scale-factor)*515.14px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01877);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928884);" role="presentation">Candida<span dir="ltr" style="left: calc(var(–scale-factor)*106.58px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911571);" role="presentation">) have necessitated the need for ne<span dir="ltr" style="left: calc(var(–scale-factor)*249.29px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94073);" role="presentation">w antifungals. <span dir="ltr" style="left: calc(var(–scale-factor)*310.03px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932488);" role="presentation">New molecular drug targets need to be explored <span dir="ltr" style="left: calc(var(–scale-factor)*512.02px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.993938);" role="presentation">the development of novel antifungal drugs. The <span dir="ltr" style="left: calc(var(–scale-factor)*283.97px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957557);" role="presentation">drug target<span dir="ltr" style="left: calc(var(–scale-factor)*330.19px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01278);" role="presentation">s are often<span dir="ltr" style="left: calc(var(–scale-factor)*377.23px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.09158);" role="presentation">ly <span dir="ltr" style="left: calc(var(–scale-factor)*390.31px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*407.71px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00179);" role="presentation">cellular proteins of <span dir="ltr" style="left: calc(var(–scale-factor)*494.02px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915662);" role="presentation">various <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922871);" role="presentation">metabolic <span dir="ltr" style="left: calc(var(–scale-factor)*114.26px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913045);" role="presentation">pathways <span dir="ltr" style="left: calc(var(–scale-factor)*154.82px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916862);" role="presentation">(like ergosterol synthesis-<span dir="ltr" style="left: calc(var(–scale-factor)*258.77px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934017);" role="presentation">, cell wall biogenesis-<span dir="ltr" style="left: calc(var(–scale-factor)*346.99px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941258);" role="presentation">, calcium-<span dir="ltr" style="left: calc(var(–scale-factor)*387.31px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93324);" role="presentation">calcineurin- <span dir="ltr" style="left: calc(var(–scale-factor)*438.10px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940496);" role="presentation">and DNA checkpoint <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90859);" role="presentation">pathways etc.), <span dir="ltr" style="left: calc(var(–scale-factor)*136.34px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950978);" role="presentation">having no significant <span dir="ltr" style="left: calc(var(–scale-factor)*225.53px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964033);" role="presentation">similarity with host proteins <span dir="ltr" style="left: calc(var(–scale-factor)*343.63px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938608);" role="presentation">to overrule the <span dir="ltr" style="left: calc(var(–scale-factor)*406.75px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955874);" role="presentation">possibility of side effects. <span dir="ltr" style="left: calc(var(–scale-factor)*515.14px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00199);" role="presentation">In <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955772);" role="presentation">this review, <span dir="ltr" style="left: calc(var(–scale-factor)*122.30px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86598);" role="presentation">some <span dir="ltr" style="left: calc(var(–scale-factor)*146.54px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926973);" role="presentation">potential <span dir="ltr" style="left: calc(var(–scale-factor)*184.61px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907473);" role="presentation">proteins <span dir="ltr" style="left: calc(var(–scale-factor)*219.89px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*231.41px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951186);" role="presentation">C. glab<span dir="ltr" style="left: calc(var(–scale-factor)*261.53px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968156);" role="presentation">rata <span dir="ltr" style="left: calc(var(–scale-factor)*281.33px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920472);" role="presentation">and their <span dir="ltr" style="left: calc(var(–scale-factor)*320.23px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892802);" role="presentation">pathways <span dir="ltr" style="left: calc(var(–scale-factor)*360.91px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924338);" role="presentation">are discussed in context to explore their <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899928);" role="presentation">potential as drug target f<span dir="ltr" style="left: calc(var(–scale-factor)*169.70px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918521);" role="presentation">or antifungal drug development.